The use of warfarin as part of antithrombotic strategy after transcutaneous aortic valve replacement is not associated with better medium-term outcomes. (3rd October 2022) - Naser, J; Gochanour, B R; Scott, C G; Luis, S A; Greason, K L; Crestanello, J A; Gulati, R; Eleid, M F; Nkomo, V T; Pislaru, S V
Abstract: Background: Bioprosthetic valve thrombosis is currently a well-recognized cause of bioprosthetic valve dysfunction. It was found to be associated with accelerated degeneration of the bioprosthesis with higher rates of valve re-replacement, even after treatment with anticoagulation. We hypothesized that the use of warfarin for three months after transcatheter aortic valve replacement (TAVR) protects against accelerated valve degeneration and is therefore associated with better outcomes compared to dual antiplatelet therapy (DAPT). Methods: Consecutive adult patients who underwent TAVR in our clinic between 2012 and 2019 were identified retrospectively. Patients with atrial fibrillation were excluded. Subsequently, patients who received DAPT were propensity matched to up to 2 patients who received three months of warfarin as part of their anti-thrombotic regimen. Matching was performed for variables that were significantly different at baseline between the two groups and included diabetes mellitus, prior myocardial infarctions, chronic lung disease, peripheral arterial disease, hemoglobin at time of TAVR, kidney function [creatinine>2], use of angiotensin-converting enzyme inhibitors / angiotensin II receptor blockers, beta blockers, the Society of Thoracic Surgeons (STS) score [STS ≥8, STS 4–8, STS<4], and valve size. The two groups were then compared for outcomes of ischemic stroke, death, valve re-replacement/intervention, the composite endpoint of the aforementioned three outcomes, as well as the three-month outcome of hemorrhagic strokes. Kaplan Meier was used for outcome analysis, and discharge date was considered time zero. Patients who had their anti-thrombotic therapy interrupted were censored at that time point. Results: A total of 1, 373 patients who underwent TAVR were identified. Of these, 576 patients with atrial fibrillation were excluded. Baseline characteristics were compared between 633 patients who received three months of warfarin and 164 patients who received DAPT after TAVR. After matching the two groups, 435 patients were included in the final analysis [warfarin in 281, DAPT in 154; median time to last follow up 2.61 years], Table 1. There was no difference in matched (Figure 1) or unmatched analysis (not shown) in outcomes of ischemic stroke, death, valve re-replacement/intervention, their composite endpoint, or hemorrhagic strokes (p>0.05 for all). Conclusion: Antithrombotic regimen including three months of warfarin after TAVR was not associated with better outcomes of ischemic strokes, deaths, and valve re-replacement/intervention or with increased risk of hemorrhagic strokes compared to DAPT. Funding Acknowledgement: Type of funding sources: None.